2 Relative value of cardiac mri and fdg-pet in treatment follow-up for cardiac sarcoidosis. (15th May 2019) - Coulden, Richard; Sonnex, Emer; Abele, Jonathan
Abstract : Introduction: 18 FDG PET-CT and cardiac MR (CMR) are described in the diagnosis of cardiac sarcoidosis (CS), each identifying different aspects of the disease. We compared PET-CT and CMR in the follow-up of patients with suspected CS. Methods: 31 patients with proven extra-cardiac sarcoidosis and possible CS were identified from the local sarcoidosis registry. All had combined PET-CT and CMR on two occasions. Selected patients had not received immunosuppressants for at least 6 months before the initial combined study. 22 patients were treated with immunosuppressants for 3 months or longer. In 9, the clinician chose not to treat or the patient refused treatment. Follow-up PET-CT and CMR were done 102-770 days later (median 228). Results: Significant myocardial FDG uptake was shown on visit 1 in 17 treated patients (myocardial SUVmax >3.6). Myocardial SUVmax fell significantly on follow-up (p<0.01) and was matched falls in FDG avid lung and node disease. Treated patients also showed improvement in left ventricular ejection fraction (LVEF) (p=0.03). 14 treated patients had late gadolinium enhancement (LGE) which was not necessarily matched by FDG. This was unchanged by visual assessment on follow-up. In 9 untreated patients (4 with FDG avid myocardium and 5 with LGE), there was no change in myocardial FDG, LGE or LVEF. Conclusion: Myocardial FDG uptake in CS represents active inflammation. When treated, this resolved or regressed on follow up with an improvement in LVEF and FDG avid thoracic disease. There was no change in extent of LGE. Untreated patients showed no change.